1978
DOI: 10.1111/j.1360-0443.1978.tb00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Some Aspects of Nutritional State in ‘hard’ Drug Addicts

Abstract: SuminarySimpte measurements of nutritional status, using portabte instruments showed that in generat, addicts did remain within fairly satifactory nutritional limits. Those preferring heroin were significantly older and heavier than those who preferred methadone by setf-injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…A multitude of previous studies have examined nutritional status among drug use populations (Aylett, 1978; Forrester, Tucker, & Gorbach, 2004, 2005; Forrester, et al, 2000; Himmelgreen, et al, 1998; McCombie, et al, 1995; Nazrul Islam, Jahangir Hossain, Ahmed, & Ahsan, 2002; Quach, et al, 2008; Santolariafernandez, et al, 1995; Tang, et al, 2010; Varela, et al, 1990). Clinical results have indicated that heroin use disorder is associated with poor nutrition and lower body mass among women (Cofrancesco, et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A multitude of previous studies have examined nutritional status among drug use populations (Aylett, 1978; Forrester, Tucker, & Gorbach, 2004, 2005; Forrester, et al, 2000; Himmelgreen, et al, 1998; McCombie, et al, 1995; Nazrul Islam, Jahangir Hossain, Ahmed, & Ahsan, 2002; Quach, et al, 2008; Santolariafernandez, et al, 1995; Tang, et al, 2010; Varela, et al, 1990). Clinical results have indicated that heroin use disorder is associated with poor nutrition and lower body mass among women (Cofrancesco, et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In many studies (HIV-positive and HIV-negative populations), drug use is associated with lower mean weight or BMI2,3,1218. In terms of differential effects of drugs, studies in two different drug using populations in Boston have shown that cocaine use (alone or mixed with opiates) is associated with lower BMI, while opiate use alone is not19,20.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that opiate addicts have poor nutritional intake and low levels of BMI and body fat [28], and several studies have reported that opiate addicts have a higher prevalence of underweight or malnutrition than usual [29,30,31]. It is acknowledged that drug abusers are often underweight and undernourished.…”
Section: Discussionmentioning
confidence: 99%